The Impact Of US Economic Sanctions On Syria And The Criteria For Lifting Them ,And The License 23 GL In Response To The Earthquake. An Analytical Study (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research has aimed at an analytical study of United States' (US) sanctions imposed on Syria before and during the Syria war, their effects on the main sectors of Syrian economy, a study of the criteria for lifting them, and the definition of US General license GL23 (180) days in response to the earthquake that Syria and Turkey were exposed to on February 6,2023, indicating to its content, the reasons behind it, and the effects of lifting US sanctions on Syria under it by using the analytical description.  This analytical study has reached that the economic sanctions imposed on Syria and the criteria for lifting them are based on economic pillars as a means to achieve illegal and inhumane political  goals imposed under the pretext of maintaining international peace and security which has had a significant negative impact on all the basic sectors of Syrian economy. The excessive compliance with the sanctions and the risk avoidance policy by banks and governments also have led to significant negative effects on the Syrian economy, and exacerbated its impact on the humanitarian situation. This unreal reducing of US sanctions on Syria under the license GL23for 180 days will not achieve the desired positive impact on the humanitarian side or rebuilding, but it has led to positive political repercussions that ended the isolation of Syria, the beating heart of Arabs, on the Arab and international levels.